Radiotherapy quality assurance of SBRT for patients with centrally located lung tumours within the multicentre phase II EORTC Lungtech trial: Benchmark case results. (March 2019) - Lambrecht, Marie; Clementel, Enrico; Sonke, Jan-Jacob; Nestle, Ursula; Adebahr, Sonja; Guckenberger, Mathias; Andratschke, Nicolaus; Weber, Damien C.; Verheij, Marcel; Hurkmans, Coen W.
Highlights: Radiotherapy quality assurance procedures improve dose coverage significantly. Delineation variation have a larger influence on PTV coverage than variations in planning and irradiation techniques. Results suggest that dose tolerance criteria should preferably take into account the accuracy of delineation. Abstract: Purpose: To report on the benchmark case (BC) study performed in the context of the European Organisation for Research and Treatment of Cancer prospective multicentre Lungtech trial of SBRT for patients with inoperable centrally located lung tumours. Methods and materials: Target volume and organs at risk (OARs) delineations first needed to be acceptable before the treatment plan was reviewed. Retrospectively, Dice similarity coefficients of the OARs and the target volumes were calculated and a set of gold standard contours adapted for each institution margins was applied on the accepted dose submissions to evaluate the influence of acceptable delineation variations on dosimetry. Results: Twenty-five institutions participated. Five BCs were accepted at the first attempt. Twenty institutions had to revise their delineation at least once and seven had to revise their planning once. The V60 Gy dose coverage improved significantly ( p  = 0.05) between the first and final submissions from median (range) 94.8% (22.5–97.8) to 95.3% (70.5–99.3). The median Dice coefficient varied significantly between OARs: The lowest values were found for the brachial plexus 0.25 (0.01–0.54) and the highest for the spinal cord 0.89 (0.71–0.95). The mean PTV Dice coefficient was 0.82 (0.48–0.92). Applying the gold standard contours, only one institution remained compliant with the dose coverage criteria with V60 Gy median (range) of 83.4% (54.2–93.9). Conclusions: Clinical guidelines and radiotherapy protocols are not a substitute for timely radiotherapy quality assurance procedures, which improve dose coverage significantly. Delineation remains the main source of BC rejection and plan review without first reviewing delineation may not be efficient. Our results show that delineation variations seem to have a larger influence on PTV coverage than variations in planning and irradiation techniques and thus suggest that dose tolerance criteria should preferably take into account the accuracy of delineation.